Differential subsampling with cartesian ordering: A high spatial-temporal resolution dixon imaging sequence for assessment of dural arteriovenous fistula - Chen, Xi; Ge, Liang; Wan, Hailinlin; Huang, Lei; Jiang, Yeqing; Lu, Gang; Wang, Jing; Zhang, Xiaolong (Frontiers in Neurology, 2022)
Objective: To evaluate the accuracy of differential subsampling with cartesian ordering (DISCO) in comparison to time of flight (TOF) in detecting Dural Arteriovenous Fistulas (DAVF），Cerebral Venous Thrombosis (CVT) and hemodynamics. Methods: 62 cases (24 female; aged 14–75; mean age, 51.3 years) were included in our study, with 42 positive and 20 negative cases via Digital Subtraction Angiography (DSA). Two neuroradiologists independently evaluated the DISCO and TOF. The sensitivity, specificity, and accuracy of the DISCO and TOF-MRA were individually calculated using DSA as the golden standard. Inter-observer reliability was assessed by using a weighted Cohen’s kappa (κ) test; P value< 0.05 was set as the threshold for statistical significance. Results: Diagnostic sensitivities of DISCO and TOF for DAVF were 92.86% and 64.29%; specificities were 95.0% and 95.0%; while accuracies were 93.55% and 74.19% respectively. For detected CVT, sensitivities of DISCO and TOF were 100% and 92.31%; specificities were 96.55% and 93.10%; with accuracies 97.62% and 92.86% respectively. In hemodynamic analysis, sensitivity of DISCO for reflux was 95.45%; with a specificity of 95.0%; and accuracy 95.24%. The inter-observer kappa values were 0.857 for DISCO (P<0.001). Conclusion: DISCO showed a high degree of sensitivity and specificity, suggesting its effectiveness in detecting DAVF with or without CVT. Intracranial hemodynamics can be identified using DISCO in DAVF patients, providing accurate evaluation of cerebral blood flow dynamics during the pre-treatment phase.